(untitled) (Theological Kronos, 2017)
The paper states that undocumented immigrant Latinos in the United States live in an almost permanent liminal state due to their immigrant status, and the social constrains of everyday. In this context, Pentecos-tal churches provide a place of refuge, empowerment, and peace by their observance of so-called gifts of the Spirit –particularly, speaking in tongues, prophecy and healing–, and the strong emphasis on the charisma which elevates to its participants to positions of leadership within the Pentecostal community.